Spatial and Temporal Variability of Polycyclic Aromatic Hydrocarbons in Sediments from Yellow River-Dominated Margin - Su Ding; Yunping Xu; Yinghui Wang; Xinyu Zhang; Liang Zhao; Jiaping Ruan; Weichao Wu (The Scientific World Journal)
Polycyclic aromatic hydrocarbons (PAHs) were analyzed for surface sediments and a sediment core from the Yellow River-dominated margin. The concentration of 16 USEPA priority PAHs in surface sediments ranged from 5.6 to 175.4 ng g−1 dry weight sediment (dws) with a mean of 49.1 ng g−1 dws. From 1930 to 2011, the distribution of PAHs (37.2 to 210.6 ng g−1 dws) was consistent with the socioeconomic development of China. The PAHs’ concentration peaked in 1964 and 1986, corresponding to the rapid economic growth in China (1958–1965) and the initiation of the “Reform and Open” policy in 1978, respectively. The applications of molecular diagnostic ratios and principal component analysis suggest that PAHs are predominantly produced by the coal and biomass combustion, whereas the contribution of petroleum combustions slightly increased after the 1970s, synchronous with an increasing usage of oil and gas in China.